2015
DOI: 10.1016/j.scr.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Impaired function of bone marrow stromal cells in systemic mastocytosis

Abstract: Patients with systemic mastocytosis (SM) have a wide variety of problems, including skeletal abnormalities. The disease results from a mutation of the stem cell receptor (c-kit) in mast cells and we wondered if the function of bone marrow stromal cells (BMSCs; also known as MSCs or mesenchymal stem cells) might be affected by the invasion of bone marrow by mutant mast cells. As expected, BMSCs from SM patients do not have a mutation in c-kit, but they proliferate poorly. In addition, while osteogenic different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…39 These results are in line with recent observations by Nemeth et al who described the presence of abnormal MSCs with slow proliferation, signs of senescence, and impaired osteogenic function (vs normal MSC colonies) in SM patients. 60 Of note, these authors did not find the KIT D816V mutation in cultured BM MSCs from any of the 5 SM patients they analyzed. The apparent discrepancy between these findings and our observations could be due to the relatively low number of patients analyzed or to a preferential growth of normal vs mutated MSCs after medium to long-term in vitro culture.…”
Section: Discussionmentioning
confidence: 88%
“…39 These results are in line with recent observations by Nemeth et al who described the presence of abnormal MSCs with slow proliferation, signs of senescence, and impaired osteogenic function (vs normal MSC colonies) in SM patients. 60 Of note, these authors did not find the KIT D816V mutation in cultured BM MSCs from any of the 5 SM patients they analyzed. The apparent discrepancy between these findings and our observations could be due to the relatively low number of patients analyzed or to a preferential growth of normal vs mutated MSCs after medium to long-term in vitro culture.…”
Section: Discussionmentioning
confidence: 88%
“…In accordance with other studies, we found c-KIT expression in granulated cells, both in the dermis and in the adventitia of collectors. The cells most likely representing mast cells [ 59 ]. CD34 clearly demarcates fibrocytes in the adventitia, which is in line with previous studies [ 28 ], and the use of CD34 as a marker for the diagnostics of fibrous tumors [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of the ABC DLBCL gene-expression signature has been proposed as a biomarker to enrich for patients with chronic active BCR signaling that are more likely to be sensitive to ibrutinib treatment, based on the higher response rate in ABC than GCB DLBCL (37% vs 5%, respectively). 4 In the study by Szydlowski et al, expression of FOXO1, which was absent in 20% of the tumors, was proposed as a potential biomarker to identify patients who should be resistant to SYK or PI3K/AKT inhibitors. Although these biomarkers are undoubtedly valuable, the majority of patients that they would select would still be expected to be unresponsive to treatment.…”
Section: 9mentioning
confidence: 99%
“…Gas6 2/2 mice are protected against lethal venous thrombosis, explained by a weakened platelet aggregation response 3 and by decreased tissue factor expression in the endothelium. 4 In the presence of endothelium-derived Gas6, tumor cells induce phosphorylation of Erk1/2 in endothelial cells, leading to an upregulation of Ptges production. Ptges produces PGE 2 from prostaglandin H 2 (PGH 2 ), which, on secretion, interacts with the EP3 receptor on platelets to trigger platelet activation and promote thrombosis.…”
Section: Kaisa E Happonen and Björn Dahlbäck Lund Universitymentioning
confidence: 99%
See 1 more Smart Citation